Palm Fatty Acid Distillate as a Potential Source for Biodiesel Production-A Review - Nazratul Zaheera, Abdul Kapor; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; M. M., Yusoff (Elsevier, 2017)
Steady escalating of global Co2 concentration and the findings of 2015 as the warmest year ever recorded, demanding feasible yet urgent solutions to counter those undesirable consequences. One of such solutions is biodiesel, regarded as much environment-friendly fuel, that to be used in diesel engines. Biodiesel is produced at industrial scale mainly from edible feedstock and attempts are constantly being made lower the feedstock cost by utilizing waste or low-cost feedstock. As to realize the effort, continuous exploration of low-cost yet viable feedstock for biodiesel production is one of the focuses of the re-searchers. Palm fatty acid distillate (PFAS) is one of such potential feedstock to be utilized in biodiesel preparation. This review serves as a gauge for the use of PFAD as a source for biodiesel production. In addition, a wide range of catalysts and the corresponding optimal reaction conditions are presented. Reusability performance of the catalysts is presented too as to evaluate the overall capability of those catalysts in driving the reaction.